2023
DOI: 10.1299/jamdsm.2023jamdsm0014
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification technique of titanium alloy to improve the tribological properties using sub-ns laser irradiation in PAO oil

Abstract: Titanium alloy is widely used in different industrial applications. For the surface modification to improve the tribological properties, laser irradiation is a promising technology, which offers high efficiency, and high automation potential and geometrical flexibility. In this study, a novel method of surface modification for titanium alloys by carbonization using low fluence of laser irradiation in the atmosphere of PAO oil is proposed. Results show that the carbon content on the surfaces significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…With detailed process design and accurate adjustment of the precursor ratio and temperature, these mature technologies are exact synthesis methods for carbide nanomaterials. Pulsed laser ablation in liquids is also a flexible method to fabricate various NPs using bulk metal targets and solutions. Moreover, femtosecond laser irradiation is a precision method of surface chemical modification, , which is becoming more and more efficient in precision surface processing, benefiting from the development of high-output lasers. , Franzel et al reported the synthesis of multiphasic inhomogeneous Mo/MoC NPs by picosecond laser ablation of Mo foil in ethanol . In this work, we irradiated a Mo substrate with a focused femtosecond laser beam in an oxygen-free organic hexane solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With detailed process design and accurate adjustment of the precursor ratio and temperature, these mature technologies are exact synthesis methods for carbide nanomaterials. Pulsed laser ablation in liquids is also a flexible method to fabricate various NPs using bulk metal targets and solutions. Moreover, femtosecond laser irradiation is a precision method of surface chemical modification, , which is becoming more and more efficient in precision surface processing, benefiting from the development of high-output lasers. , Franzel et al reported the synthesis of multiphasic inhomogeneous Mo/MoC NPs by picosecond laser ablation of Mo foil in ethanol . In this work, we irradiated a Mo substrate with a focused femtosecond laser beam in an oxygen-free organic hexane solution.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser ablation in liquids is also a flexible method to fabricate various NPs using bulk metal targets and solutions. 34 36 Moreover, femtosecond laser irradiation is a precision method of surface chemical modification, 37 , 38 which is becoming more and more efficient in precision surface processing, benefiting from the development of high-output lasers. 39 , 40 Franzel et al reported the synthesis of multiphasic inhomogeneous Mo/MoC NPs by picosecond laser ablation of Mo foil in ethanol.…”
Section: Introductionmentioning
confidence: 99%